Drought and salinity alter endogenous hormonal profiles at the seed germination phase. Issue 1 (1st December 2015) - Llanes, Analía; Andrade, Andrea; Masciarelli, Oscar; Alemano, Sergio; Luna, Virginia
Abstract: The most critical phase in plant life is seed germination, which is influenced by environmental factors. Drought and salinity are key environmental factors that affect seed germination. Reduction or alterations of germination when seeds are exposed to these factors have been shown to be due to either the adverse effects of water limitation and/or specific ion toxicity on metabolism. Phytohormones are chemical messengers produced within the plant that control its growth and development in response to environmental cues; small fluctuations of phytohormone levels alter the cellular dynamics and, hence, play a central role in regulating plant growth responses to these environmental factors. To integrate current knowledge, the present review focuses on the involvement of endogenous phytohormones in plant adaptative responses to drought and salinity at one of the plant's developmental phases.